Pengembangan Perangkat Pembelajaran Menggunakan Model Pembelajaran Scientific Inquiry Berbasis Budaya Melayu untuk Meningkatkan Self-Efficacy Mahasiswa - Putrini R Harahap, Saima; Kurnila, Nely (Journal Of Education And Teaching Learning (JETL), 2025)
The goal to be achieved is the increase in student self-efficacy through the development of learning tools using a scientific inquiry learning model based on Malay culture. This research is categorized into types of development research. The developed device uses a 4-D model. This research was conducted in the Mining Technology Study Program at the Ketapang State Polytechnic, class 1-B, with 28 students. According to the results of expert validation, the learning tools that have been developed in this research are of good quality and meet valid criteria by the validator, so they are suitable for use as learning tools. Implementation of learning tools in the practical category (very good). More than 80% of student responses were positive towards learning. The average student self-efficacy questionnaire results showed an increase from pretest to posttest in Trial II, with the pretest score being 83.43 and the posttest score reaching 119.32, out of a maximum score of 140. Based on these results, it can be concluded that student self-efficacy improved after implementing the learning devices using the scientific inquiry model based on Malay culture, as evidenced by the increase in scores from the pre-test to the post-test in Trial II.